(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the life and scientific activity of the outstanding scientist honorary academician in a number of great linguists Orusbaeva Bubaina Omurzakova who dedicated her life to her native language has made an inordinate contrition to a profound study of the national language from a scientific point of view.